GENERASI MUDA YANG BERKARAKTER MELALUI PENDIDIKAN AGAMA HINDU - Setyaningsih (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2019)
Character is a fundamental value that cannot be released in the formation of individual personalities. Perfectly formed characters can realize the quality of human resources that have the potential to achieve progress. Law Number 20 Year 2003 concerning the national education system article 3 which requires the formation of character from an early age. Hindu religious education is a sub-system of national education. Hindu religious education is an attempt to produce intelligent students both intellectually, emotionally, and spiritually. In the practice of religion, it cannot be separated from the Three Basic Frameworks of Hinduism, namely Tattva, Su??la, and ?c?ra, when understood, internalized, and implemented will make Hindus have good and noble personalities. In addition, many teachings from Hinduism that can shape human character include Tri Kaya Parisudha, Chess Vidya, Chess Marga and Chess ??rama. Therefore, the revitalization of religious education in schools must be pursued for the intended purpose. Through quality Hindu religious education, it is expected to be able to form a young generation of character. There are 6 ways of doing revitalization in Hindu Religious Education, namely: (1) PAH learning model with consequential dimension approach; (2) the approach to the dimension of imperensia; (4) Ritualistic dimension approach; (5) intellectual dimension approach; (6) teaching and learning achievement evaluation model that illustrates the level of competence of students with Hindu characters.